Composite electrolyte membrane for zinc-air battery and preparation method of composite electrolyte membrane
By using a composite electrolyte membrane composed of nanocellulose zinc sulfonate and hydrophilic polymer in zinc-air batteries, the problems of severe side reactions and short cycle life in zinc-air batteries are solved, and the battery performance is improved and the cycle life is extended.
Patent Information
- Application Number
- CN202510042105.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
The existing zinc-air batteries have severe side reactions due to the use of alkaline electrolytes, low utilization rate of zinc negative electrodes, short cycle life, and excessive free water in neutral water electrolytes lead to a decrease in ionic conductivity, affecting battery performance.
A composite electrolyte membrane composed of nanocellulose zinc sulfonate and hydrophilic polymer is used to coat the surface of nanocellulose zinc sulfonate through hydrophilic polymer to construct a "high-oriented" water-retaining layer, reducing free water content, reducing water volatility, and improving the reversibility of zinc negative electrode.
Effectively extend the cycle life of zinc-air batteries, inhibit side reactions such as hydrogen evolution, corrosion and dendrite growth, improve the reversibility of zinc negative electrodes, and ensure the rapid transmission of zinc ions.
Smart Images

Figure CN119833833A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical energy storage, and in particular relates to a composite electrolyte membrane for a zinc-air battery and a preparation method thereof. Background Art
[0002] Energy storage systems represented by lithium-ion batteries have been widely used in the fields of power batteries and large-scale energy storage. However, the current lithium-ion battery technology is far from perfect, and there are still problems such as high cost, low energy density and poor safety. Zinc-air batteries have a high theoretical energy density (1086Wh kg -1 ), good safety, low cost, and environmental friendliness make it an important choice for the next generation of batteries. Especially with the booming development of flexible and wearable electronic devices, the development of rechargeable zinc-air batteries with high energy density and long cycle life is of great practical significance.
[0003] Zinc-air battery is a semi-enclosed battery with zinc as the negative electrode and oxygen as the active substance participating in the positive electrode reaction. Although primary alkaline zinc-air batteries have been commercialized and successfully applied in fields such as medical and communications, such as miniature hearing aids and wireless information transmission devices, electrochemically reversible rechargeable zinc-air batteries are still in the laboratory research and development stage due to many challenges. In recent years, research in the field of zinc-air batteries has mainly focused on the development of efficient bifunctional catalysts. However, the development of electrolytes that limit the reversibility and cycle life of zinc-air batteries has long been neglected. Zinc-air batteries currently mainly use aqueous electrolytes, represented by high-concentration strong alkaline electrolytes (201910198661.2; 202120808087.0). There are still a series of side reactions in the alkaline electrolyte system: the metal zinc negative electrode reacts with hydroxide ions on the electrode surface in the alkaline electrolyte to form a zinc oxide passivation layer, which reduces the utilization rate of the zinc negative electrode and causes the actual capacity of the zinc-air battery to be far lower than the theoretical capacity; the alkaline electrolyte easily reacts with carbon dioxide in the air to form insoluble carbonates on the surface of the positive electrode, blocking the reaction channel of the air electrode. Non-alkaline electrolyte systems, especially mild and environmentally friendly neutral aqueous electrolytes, can reduce a series of side reactions in alkaline electrolytes (Angew. Chem. Int. Ed. 2022, 61, e202207353). Therefore, the development of highly stable neutral aqueous electrolytes is an inevitable route to improve the reversibility and cycle life of zinc-air batteries.
[0004] However, due to the presence of a large amount of free water in traditional neutral aqueous electrolytes, the zinc negative electrode usually has side reactions such as hydrogen evolution and corrosion, which affect the reversibility of the battery. In addition, unlike conventional zinc-ion batteries, zinc-air batteries are a semi-closed system. During long-term operation, the water in the electrolyte will evaporate, resulting in a decrease in ionic conductivity and an increase in the internal resistance of the battery. This is also one of the important reasons for the decline in battery performance and battery failure. Therefore, reducing the content of free water and developing a neutral quasi-solid electrolyte system with excellent water retention performance is the key to extending the cycle life of zinc-air batteries. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a composite electrolyte membrane for zinc-air batteries and a preparation method thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A composite electrolyte membrane for a zinc-air battery. The composite electrolyte membrane is a composite electrolyte comprising nano-cellulose zinc sulfonate and a hydrophilic polymer, wherein the hydrophilic polymer is coated on the surface of the nano-cellulose zinc sulfonate.
[0008] The mass ratio of the nanocellulose zinc sulfonate to the hydrophilic polymer is 10:(0.5-50), preferably 10:(5-20).
[0009] The length of the nano-cellulose zinc sulfonate is 0.2-5 μm, the diameter is 2-100 nm, and the content of the zinc sulfonate group is 0.2-2.5 mmol / g.
[0010] Preferably, the length of the nano-cellulose zinc sulfonate is 0.5-1 μm; the diameter of the nano-cellulose zinc sulfonate is 5-20 nm; and the content of zinc sulfonate groups in the nano-cellulose zinc sulfonate is 1.0-1.8 mmol / g.
[0011] The hydrophilic polymer meets at least one of the following conditions:
[0012] (1) The molecular weight of the hydrophilic polymer is 200-5000000;
[0013] (2) The hydrophilic polymer molecular structure contains one or a combination of hydroxyl, amino, amide, sulfonic acid, phosphoric acid, carboxyl, and quaternary ammonium groups.
[0014] Preferably, the hydrophilic polymer is selected from one or a combination of polyethylene glycol, polyacrylamide, polyvinyl alcohol, polyglycerol, polyacrylic acid, and quaternized polymers.
[0015] More preferably, it is one or more of polyethylene glycol, polyacrylamide or polyvinyl alcohol.
[0016] A method for preparing a composite electrolyte membrane for a zinc-air battery comprises dispersing nanocellulose zinc sulfonate in water to prepare a nanocellulose zinc sulfonate dispersion, adding a hydrophilic polymer thereto, stirring and dissolving the dispersion, and centrifuging at a high speed (2000-15000 rpm) for 5-30 minutes, re-dispersing the collected lower layer of the centrifuge in water to form a membrane, and drying to obtain a water-retaining electrolyte membrane in which the hydrophilic polymer is coated on the surface of the nanocellulose zinc sulfonate.
[0017] The concentration of the nano-cellulose zinc sulfonate dispersion is 1%-10% by mass, preferably 2%-5% by mass.
[0018] The film forming method is one of a casting method, a suction filtration method, a blade coating method or a spin coating method.
[0019] An application of the composite electrolyte membrane for zinc-air batteries, and an application of the composite electrolyte membrane in zinc-air batteries.
[0020] The zinc-air battery is an aqueous zinc-air battery or a solid-state zinc-air battery.
[0021] A zinc-air battery contains the composite electrolyte membrane.
[0022] The beneficial effects of the present invention are:
[0023] The composite electrolyte membrane of the present invention is composed of nano-cellulose zinc sulfonate and a hydrophilic polymer. Through the interaction between the hydrophilic group in the polymer chain and the sulfonate group on the nano-cellulose, the hydrophilic polymer is adsorbed on the surface of the nano-cellulose zinc sulfonate to construct a "highly oriented" water-retaining layer. Through the hydrogen bond interaction between the hydrophilic polymer and the water molecules, the hydrophilic polymer can reduce the content of free water, reduce the volatilization of water, and effectively extend the cycle life of the zinc-air battery. At the same time, due to the reduction of the free water content, the water-retaining electrolyte membrane can effectively inhibit the side reactions such as hydrogen evolution, corrosion and dendrite growth, and improve the reversibility of the zinc negative electrode. In addition, the polymer water-retaining layer also serves as a one-dimensional fast ion channel for zinc ions, ensuring the rapid transmission of zinc ions under low water content. More importantly, in the electrolyte material provided by the present invention, the zinc ions are completely provided by the nano-cellulose zinc sulfonate, and no metal zinc salt needs to be added, which simplifies the electrolyte preparation process. The electrolyte can be used only by absorbing moisture in humid air. The design of the macromolecular zinc salt can also increase the zinc ion migration number, avoiding the side reactions such as electrode polarization and passivation caused by free anions. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of preparing the composite electrolyte membrane provided by an embodiment of the present invention.
[0025] Figure 2 1 is a scanning electron microscope image of the nanocellulose zinc sulfonate-polyacrylamide composite electrolyte membrane in Example 1 provided in the embodiments of the present invention, wherein A is a scanning electron microscope image of a cross section of the composite electrolyte membrane, and B is a partial enlarged image of A.
[0026] Figure 3 These are the test results of the water retention rate of the electrolytes in Examples 1-3 of the present invention and Comparative Example 1.
[0027] Figure 4 This is the long cycle curve of the zinc-air battery assembled with the nanocellulose zinc sulfonate-polyacrylamide composite electrolyte at room temperature in Example 1 provided in the embodiments of the present invention.
[0028] Figure 5 This is the long cycle curve of the zinc-air battery assembled with the nanocellulose zinc sulfonate-polyethylene glycol composite electrolyte in Example 2 provided in the embodiments of the present invention at room temperature.
[0029] Figure 6 This is the long cycle curve of the zinc-air battery assembled with the nanocellulose zinc sulfonate-polyvinyl alcohol composite electrolyte in Example 3 provided in the embodiments of the present invention at room temperature.
[0030] Figure 7 This is the long cycle curve of the zinc-air battery assembled with the nanocellulose zinc sulfonate electrolyte in Comparative Example 1 provided in the embodiment of the present invention at room temperature.
[0031] Figure 8 This is the long cycle curve of the zinc-air battery assembled with the nanocellulose zinc sulfonate-polyacrylamide electrolyte at room temperature in Comparative Example 2 provided in the embodiment of the present invention.
[0032] Fig. 9 This is the long cycle curve of the zinc-air battery assembled with the nanocellulose zinc sulfonate-polyepichlorohydrin electrolyte at room temperature in Comparative Example 3 provided in the embodiment of the present invention. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below through specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The hydrophilic polymer in the electrolyte membrane of the present invention constructs a "highly oriented" water-retaining layer on the surface of nanocellulose zinc sulfonate, and reduces the free water content and water volatilization through the hydrogen bond interaction between the hydrophilic polymer and water molecules, and at the same time can improve the reversibility of the zinc negative electrode and effectively extend the cycle life of the zinc-air battery. In addition, the polymer water-retaining layer also serves as a one-dimensional fast ion channel for zinc ions, ensuring the rapid transmission of zinc ions at low water content.
[0035] Water retention test: After the electrolyte membrane is completely dried, it is weighed as m0. Then the electrolyte membrane is placed in a desiccator at a relative humidity of 75% and balanced for 24 hours, and then weighed as m1. Then the electrolyte membrane is transferred to a desiccator at a relative humidity of 30% and weighed every 2 hours. The weight is recorded as m t , then the water retention rate at the corresponding time = (m t -m0) / (m1-m0)
[0036] Example 1
[0037] like Figure 1 As shown in the preparation process, 5 g of nanocellulose zinc sulfonate was dispersed in water to prepare a 5 wt% dispersion, and then 2.5 g of polyacrylamide (Mn = 10000) was added thereto. After sufficient stirring to dissolve, the dispersion was centrifuged at high speed (8000 rpm) for 15 minutes. The lower layer of the centrifuge was redispersed in water and dried in an oven at 60°C by a casting method to form a film (see Figure 2 ).
[0038] The cross-sectional SEM images of the obtained composite membrane are shown in Figure 2 As shown, Figure 2 The thickness of the membrane shown in A is about 25 μm. After local magnification, fibrous nanocellulose zinc sulfonate can be seen in Figure B, and its surface is evenly coated with the polymer.
[0039] like Figure 3 As shown, the water retention rate of the membrane after 12 hours was 83%. After the membrane was placed in an environment with a relative humidity of 75% for 24 hours, the zinc ion conductivity at room temperature was 5mS / cm and the zinc ion migration number was 0.85.
[0040] The composite electrolyte membrane after balanced water absorption was then assembled into a zinc-air battery with a zinc metal anode and an air cathode (Ru@KB). 2 The charge and discharge performance of the battery is tested at a current density of Figure 4 The battery's charge and discharge overpotential is about 0.8V, and it can be cycled stably for more than 1500h.
[0041] Example 2
[0042] Take 5g of nanocellulose zinc sulfonate and disperse it in water to prepare a 5wt% dispersion. Then add 2.5g of polyethylene glycol (Mn=600) thereto, stir thoroughly to dissolve and centrifuge at high speed (8000 rpm) for 15 minutes. Re-disperse the lower layer of the centrifuge in water and dry it in an oven at 60°C to form a film using a casting method.
[0043] like Figure 3 As shown, the water retention rate of the membrane after 12 hours was 72%. After the membrane was placed in an environment with a relative humidity of 75% for 24 hours, the zinc ion conductivity at room temperature was 6 mS / cm and the zinc ion migration number was 0.78.
[0044] The composite electrolyte membrane after balanced water absorption was then assembled into a zinc-air battery with a zinc metal anode and an air cathode (Ru@KB). 2 The charge and discharge performance of the battery is tested at a current density of Figure 5 The battery's charge and discharge overpotential is about 0.7V, and it can be cycled stably for more than 1400h.
[0045] Example 3
[0046] Take 5g of nanocellulose zinc sulfonate and disperse it in water to prepare a 5wt% dispersion, then add 2.5g of polyvinyl alcohol (Mn=5000) thereto, stir thoroughly to dissolve and centrifuge at high speed (8000 rpm) for 15 minutes, re-disperse the lower layer of the centrifuge in water and dry it in an oven at 60°C to form a film by a casting method.
[0047] like Figure 3 As shown in the figure, the water retention rate of the membrane after 12 hours was 78%. After the membrane was placed in an environment with a relative humidity of 75% for 24 hours, the zinc ion conductivity at room temperature was 4mS / cm and the zinc ion migration number was 0.82. The composite electrolyte membrane after equilibrium water absorption was then assembled with a zinc metal negative electrode and an air positive electrode (Ru@KB) to form a zinc-air battery, and the battery was tested at 0.1mA / cm 2 The charge and discharge performance of the battery is tested at a current density of Figure 6 The battery's charge and discharge overpotential is about 0.9V, and it can be cycled stably for more than 1200h.
[0048] Comparative Example 1
[0049] 5 g of nanocellulose zinc sulfonate was dispersed in water to prepare a 5 wt % dispersion, and the dispersion was dried in an oven at 60° C. using a casting method to form a film.
[0050] like Figure 3As shown in the figure, since the surface of nanocellulose is not coated with hydrophilic polymer, the water retention rate of the membrane is only 8% after 12 hours. After the membrane is placed in an environment with a relative humidity of 75% for 24 hours, the zinc ion conductivity at room temperature is measured to be 1mS / cm and the zinc ion migration number is 0.70.
[0051] The composite electrolyte membrane after balanced water absorption was then assembled into a zinc-air battery with a zinc metal anode and an air cathode (Ru@KB). 2 The charge and discharge performance of the battery is tested at a current density of Figure 7 The charge and discharge overpotential of the battery in the first 50 hours is about 1.2V. As the cycle continues, the overpotential increases to more than 2V, and the battery fails after 120 hours.
[0052] Comparative Example 2
[0053] 5g of nanocellulose zinc sulfonate was dispersed in water to prepare a 5wt% dispersion, and then 2.5g of polyacrylamide (Mn=10000) was added thereto. After sufficient stirring and dissolution, the film was dried in an oven at 60°C by a casting method. After the film was placed in an environment with a relative humidity of 75% for 24 hours, the zinc ion conductivity at room temperature was measured to be 3mS / cm, and the zinc ion migration number was 0.75.
[0054] Compared with Example 1, the main reason for the decrease in zinc ion conductivity of the membrane is that the hydrophilic polymer not adsorbed on the surface of nanocellulose zinc sulfonate is not removed, resulting in an increase in the internal viscosity of the membrane after water absorption, which hinders the transmission of zinc ions. The composite electrolyte membrane after balanced water absorption was then assembled with a zinc metal negative electrode and an air positive electrode (Ru@KB) to form a zinc-air battery, and the battery was tested at 0.1 mA / cm 2 The charge and discharge performance of the battery is tested at a current density of Figure 8 As shown in the figure, the charge and discharge overpotential of the battery is about 0.7V, and the battery fails after about 620h of cycling.
[0055] Comparative Example 3
[0056] 5g of nanocellulose zinc sulfonate was dispersed in water to prepare a 5wt% dispersion, and then 2.5g of polyepichlorohydrin (Mn=10000) was added thereto. After sufficient stirring and dissolution, the dispersion was centrifuged at high speed (8000 rpm) for 15 minutes. The lower layer of the centrifuge was redispersed in water and dried in an oven at 60°C by a casting method to form a film. After the film was placed in an environment with a relative humidity of 75% for 24 hours, the zinc ion conductivity at room temperature was measured to be 0.8mS / cm, and the zinc ion migration number was 0.72.
[0057] The composite electrolyte membrane after balanced water absorption was then assembled into a zinc-air battery with a zinc metal anode and an air cathode (Ru@KB). 2 The charge and discharge performance of the battery is tested at a current density of Fig. 9 As shown in the figure, the battery's initial charge and discharge overpotential reaches about 1.2V, and after 50 cycles, the charge and discharge overpotential reaches more than 2V.
Claims
1. A composite electrolyte membrane for a zinc-air battery, characterized in that: The composite electrolyte membrane is a composite electrolyte comprising nano-cellulose zinc sulfonate and a hydrophilic polymer, wherein the hydrophilic polymer is coated on the surface of the nano-cellulose zinc sulfonate.
2. The composite electrolyte membrane for zinc-air battery according to claim 1, characterized in that: The mass ratio of the nano-cellulose zinc sulfonate to the hydrophilic polymer is 10:(0.5-50).
3. The composite electrolyte membrane for zinc-air battery according to claim 1 or 2, characterized in that: The length of the nano-cellulose zinc sulfonate is 0.2-5 μm, the diameter is 2-100 nm, and the content of the zinc sulfonate group is 0.2-2.5 mmol / g.
4. The composite electrolyte membrane for zinc-air battery according to claim 1 or 2, characterized in that: The hydrophilic polymer meets at least one of the following conditions: (1) The molecular weight of the hydrophilic polymer is 200-5000000; (2) The hydrophilic polymer molecular structure contains one or a combination of hydroxyl, amino, amide, sulfonic acid, phosphoric acid, carboxyl, and quaternary ammonium groups.
5. The composite electrolyte membrane for zinc-air battery according to claim 4, characterized in that: The hydrophilic polymer is selected from one or a combination of polyethylene glycol, polyacrylamide, polyvinyl alcohol, polyglycerol, polyacrylic acid, and quaternary ammonium polymers.
6. A method for preparing a composite electrolyte membrane for a zinc-air battery according to claim 1, characterized in that: Nanocellulose zinc sulfonate is dispersed in water to prepare a nanocellulose zinc sulfonate dispersion, a hydrophilic polymer is added thereto, the dispersion is fully stirred and dissolved, and then centrifuged at a high speed, the lower layer of the centrifuge is redispersed in water to form a film, and after drying, a water-retaining electrolyte membrane with the hydrophilic polymer coated on the surface of the nanocellulose zinc sulfonate is obtained.
7. The method for preparing a composite electrolyte membrane for a zinc-air battery according to claim 6, characterized in that: The concentration of the nano-cellulose zinc sulfonate dispersion is 1%-10% by mass.
8. An application of the composite electrolyte membrane for zinc-air batteries according to claim 1, characterized in that: Application of composite electrolyte membranes in zinc-air batteries.
9. Use of the composite electrolyte membrane for zinc-air batteries according to claim 8, characterized in that: The zinc-air battery is an aqueous zinc-air battery or a solid-state zinc-air battery.
10. A zinc-air battery, characterized in that: A composite electrolyte membrane comprising the composite electrolyte membrane according to claim 1.
Citation Information
Patent Citations
High-stability electrolyte for zinc-air battery and preparation method of high-stability electrolyte
CN110729527A
Wearable flexible rechargeable zinc-air battery
CN214706057U